PEMANFAATAN MINI KOMPUTER RASPBERRY SEBAGAI NETWORK MONITORING TOOL PORTABLE - Suharyanto, Cosmas Eko; Gopama, Viriyadharma (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
This study aims to design a portable monitoring system using the Raspberry mini computer. As a case study, we conducted this research at Credit Union Tunas Harapan, which is based in Batam, Indonesia. We implemented the system with additional tools to monitor networks, namely Wireshark and Nagios. On the local network, we managed to monitor broadcasting from the switch. We have also analyzed several issues on network security. The use of architectural Raspberry mini computers is a very flexible tool.